The Importance of Vehicle Mobility Settings for VANET: Mini Review - Yogarayan, Sumendra; Abdul Razak, Siti Fatimah; Azman, Afizan; Abdullah, Mohd. Fikri Azli (International Journal of Human and Technology Interaction (IJHaTI), 2021)
The configurations of nodes transmitting wirelessly, show a noteworthy effect in the evaluation of vehicle ad hoc networks (VANET). Although significant research has led to the development of simulations that are more relevant to real-world mobility, the level of information required to demonstrate VANET still remains open. This paper aims to discover the significance of vehicle mobility in VANET that depend on vehicle density, environmental settings and vehicle speed. This considerably helps researchers to better characterise vehicle mobility for VANET deployments.